Bryce’s Character Development in Wendelin van Draanen’s Flipped: A Structural Approach - Karina, Kartika Chandra (English Literature Study Program, 2023)
In the novel, the portrayal of the character consistently can be seen in the plot. To indicate each character in a story, the plot can affect a person in the development of characteristics. Some events from time to time make a person's character change naturally. The author uses Flipped by Wendelin Van Draanen which was published by Knopf Book in 2001 as the object of the thesis. This research has several objectives. Those are to find out Bryce’s character, to find out the plot of Flipped, and to find out the character development of Bryce through the plot. This research has several results, namely the character of Bryce at the beginning of the plot, which is very terrible. Several events in the plot of the novel make Bryce change a lot. Those who were prejudiced became open-minded people, cowards became brave people, irresponsible people became responsible people, and apathetic became people who took the initiative.